2021
DOI: 10.1080/00223891.2021.1981346
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of the Reflective Functioning Questionnaire (RFQ)

Abstract: The Reflective Functioning Questionnaire (RFQ) is an 8-item self-report measure of reflective functioning that is presumed to capture individual differences in hypo-and hypermentalizing. Despite its broad acceptance by the field, we argue that the validity of the measure is not well-established. The current research elaborates on problems of the RFQ related to its item content, scoring procedure, dimensionality, and associations with psychopathology. We tested these considerations across three large clinical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(134 citation statements)
references
References 47 publications
21
98
0
Order By: Relevance
“…Conversely, these scores were all positively correlated with uncertainty about mental states (RFQ-8). Consistent with previous work (e.g., Müller et al, 2021), The effect sizes for these associations tended to be quite large.…”
Section: Collabra: Psychologysupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, these scores were all positively correlated with uncertainty about mental states (RFQ-8). Consistent with previous work (e.g., Müller et al, 2021), The effect sizes for these associations tended to be quite large.…”
Section: Collabra: Psychologysupporting
confidence: 90%
“…Furthermore, in contrast to the rest of the mentalizing dimensions which were behaviorally probed, certainty/uncertainty was the only mentalizing dimension which we measured by self-report. The relatively stronger associations observed between this dimension and psychopathology may therefore be due to the specific wording of key items on the RFQ (see Müller et al, 2021), or, at least in part, to the fact that behavioral and self-report measures tend to be weakly correlated (see Dang et al, 2020). On the other hand, the remarkably consistent patterns observed in our data underscores the extent to which the certainty/uncertainty dimension may be promising for future investigation of the relationship between mentalizing tendencies and psychopathology.…”
Section: Collabra: Psychologymentioning
confidence: 99%
“…For example, when predicting personality dysfunction by means of certainty about mental states, both low and high levels of certainty would be associated with high dysfunction, whereas middle levels of certainty would exhibit low dysfunction. Previous research, however, found no evidence for such associations using the RFQ (Müller et al, 2021;. Second, irrespective of the fallible nature of knowing oneself and others (e.g., Vazire, 2010), we argue that individuals should, in general, find it easier to perceive and interpret their own mental states as compared to others' mental states (e.g., Thornton et al, 2019) because others' mental states need to be inferred from external cues, whereas individuals can directly experience their own mental states consciously.…”
Section: Developing the Certainty About Mental States Questionnaire (Camsq)mentioning
confidence: 80%
“…This could suggest that MDers hypermentalize less, but several studies have criticized the use of this factor as a true index of hypermentalization in the general population. In fact, it appears that the Certainty factor is instead associated with a good mentalization functioning [ 23 , 54 , 55 ]. Our study appears to confirm this.…”
Section: Discussionmentioning
confidence: 99%